Histochemistry of backcross 1 of oil palm seeds at different storage periods - Ernayunita Ernayunita; Taryono Taryono; Prapto Yudono (Jurnal Ilmu Pertanian, 2020)
Oil palm backcross 1 is the result of the crossing between Elaeis oleifera and Elaeis guineensis, followed by backcrossing to one of its parents. It has several advantages, including slow height growth and good oil quality, thereby having the potential to be developed. However, it also has a short seed shelf life, which might be inherited from E. oleifera that has relatively quick seed deterioration. This is problem to the breeding program, and there have not been many studies on the seed deterioration process. A histological examination can determine the composition of food reserves in seed endosperm tissue. Therefore, it is necessary to assess the histochemistry of seeds concerning the process of seed deterioration. Histochemical tests with Sudan III, Milon, and IKI reagents were used as histochemical tests of fat, protein and carbohydrate seed content with different seed storage periods, i.e. 4, 3, 2, and less than 1 year. The result showed that the fat content decreased during the storage periods. Based on carbohydrates and proteins staining, there were only very few substances , which were difficult to distinguish among the storage periods, so that this analysis could not be used as the determining indicator of seed deterioration. The fat content was a determining factor of seed deterioration and quality. The oil palm seed storage up to 3-4 years led to the reduction in the fat content in significant quantities compared to the fresh seeds stored less than 1 year as they still contained a lot of fat in the cell.